2019
DOI: 10.1111/1467-8462.12345
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Climate on Migration

Abstract: This paper provides an overview of research into the phenomenon of whether climatic factors, such as temperature and weatherrelated disasters, affect the decision to migrate. As an example, we examine migration flows from 198 countries to Australia for the time span from 1980 to 2015. Our results show that temperature does not have a robust, significant effect on migration flows, while weather-related disasters do significantly affect flows to Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yet flooding (Call et al, 2017; Chen et al, 2017; Chen & Mueller, 2019; Ocello et al, 2015), droughts (Cottier & Salehyan, 2021; Ocello et al, 2015; Quiñones et al, 2021) and temperature (Beine & Parsons, 2017; Mueller et al, 2020; Nawrotzki & Bakhtsiyarava, 2017; Nguyen, 2021) and precipitation fluctuations (Beine & Parsons, 2015; Call et al, 2017; Call & Gray, 2020; Thiede et al, 2016) have also each been found to be associated with decreased migration. Other studies have found no, insignificant, or inconsistent migration effects from flooding (Bohra‐Mishra et al, 2014; Gray & Mueller, 2012; Mueller et al, 2014), storms (Loebach, 2016; Wesselbaum, 2019), droughts (Owain & Maslin, 2018; Selby, 2019), and precipitation fluctuations (Bohra‐Mishra et al, 2017; De Longueville et al, 2019; Grace et al, 2018; Gray & Wise, 2016; Mueller et al, 2020). The evidence here supports the IPCC's “high confidence” observation that “climate‐related migration outcomes are diverse … and may be manifest as decreases or increases in migration flows” (IPCC, 2022, p. 1079).…”
Section: Short‐term Shocksmentioning
confidence: 96%
See 2 more Smart Citations
“…Yet flooding (Call et al, 2017; Chen et al, 2017; Chen & Mueller, 2019; Ocello et al, 2015), droughts (Cottier & Salehyan, 2021; Ocello et al, 2015; Quiñones et al, 2021) and temperature (Beine & Parsons, 2017; Mueller et al, 2020; Nawrotzki & Bakhtsiyarava, 2017; Nguyen, 2021) and precipitation fluctuations (Beine & Parsons, 2015; Call et al, 2017; Call & Gray, 2020; Thiede et al, 2016) have also each been found to be associated with decreased migration. Other studies have found no, insignificant, or inconsistent migration effects from flooding (Bohra‐Mishra et al, 2014; Gray & Mueller, 2012; Mueller et al, 2014), storms (Loebach, 2016; Wesselbaum, 2019), droughts (Owain & Maslin, 2018; Selby, 2019), and precipitation fluctuations (Bohra‐Mishra et al, 2017; De Longueville et al, 2019; Grace et al, 2018; Gray & Wise, 2016; Mueller et al, 2020). The evidence here supports the IPCC's “high confidence” observation that “climate‐related migration outcomes are diverse … and may be manifest as decreases or increases in migration flows” (IPCC, 2022, p. 1079).…”
Section: Short‐term Shocksmentioning
confidence: 96%
“…Across these different types, findings are mixed and in some cases contradictory, with evidence indicating that shocks may be associated with increased migration in some contexts (or for some social groups) but decreased migration in (or for) others. Thus, flooding (Beine & Parsons, 2015; Kakinuma et al, 2020; Robalino et al, 2015; Wesselbaum, 2019), storms (Berlemann & Tran, 2021; Pajaron & Vasquez, 2020; Spencer & Urquhart, 2018), droughts (Baez et al, 2017; Defrance et al, 2022; Fishman & Li, 2022; Murray‐Tortarolo & Salgado, 2021), positive and/or negative temperature fluctuations and extremes (Baronchelli & Ricciuti, 2022; Bohra‐Mishra et al, 2017; Cai et al, 2016; Call et al, 2017; Call & Gray, 2020; Falco et al, 2019; Mueller et al, 2014; Thiede et al, 2016; Wesselbaum, 2019), and precipitation fluctuations (Coniglio & Pesce, 2015; Cottier & Salehyan, 2021; Leyk et al, 2017; Nawrotzki & Bakhtsiyarava, 2017; Nguyen, 2021) have each been associated in multiple studies with increased migration and displacement. Climate‐related shocks may have a delayed impact on migration decisions, with studies showing that the effects of storms (Pajaron & Vasquez, 2020; Spencer & Urquhart, 2018) and rainfall fluctuations (Hunter et al, 2013; Thiede et al, 2016) on migration is lagged (e.g., increasing one or two years later).…”
Section: Short‐term Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on international migration revealed differing findings, underlining the importance of context and methodology. For example, Wesselbaum [30 ] examines migration flows from 198 countries to Australia showing that temperature does not have a robust, significant effect on migration flows, while weather-related disasters do…”
Section: Mobility In Spacementioning
confidence: 99%